A NOTE ON FULL TRANSFORMATION SEMIGROUPThe topics in this paper deal with generating subsemigroups of the full transformation semigroup ????(????) on a totally ordered finite set (????, ≤) with an arbitrary equivalence relation ???? defined on it. Using the equiv - EDEGHAGBA, ELIJAH. E.; ADEBAYO, SALAUDEEN A.; MUHAMMAD, UMAR F. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The topics in this paper deal with generating subsemigroups of the full transformation semigroup ????(????) on a totally ordered finite set (????, ≤) with an arbitrary equivalence relation ???? defined on it. Using the equivalence relation on the set and the cardinality of the set, we investigate under what conditions some of these subsemigroups of ????(????) generated are equal.